System of comprehensive evaluation of academic staff activity - Dudarev, Igor (Mukachevo State University, 2024)
Universities evaluate the activities of academic staff annually to encourage excellence in performance and to develop training programmes to enhance their professional skills. The evaluation of academic staff activities is mainly based on the results of their scientific work, but it is important to take into account other areas of their responsibilities. Therefore, the purpose of the study was to develop a system for the comprehensive evaluation of academic staff, which would consider the outcomes of their pedagogical, methodological, scientific, and organisational work. The method employed involved the analysis of university regulatory documents that define academic staff evaluation systems. Graphs were utilised to model the structure of the relationships between the criteria of the proposed evaluation system. The evaluation system determines the indices of academic staff work efficiency both for individual types of activities an comprehensively. According to the system, the outcomes of all academics are compared with the best results achieved in the current year at the university or national level. The calculations of the comprehensive index of activity efficiency for each academic enable the formation of university, faculty, and departmental rankings of academic staff, as well as the categorisation of performance levels based on the proposed scale. It was recommended that the evaluation results be presented in academic portfolios on the university website to ensure transparency. This approach also enables stakeholders to track changes in academics’ effectiveness over time. The evaluation system will enhance personnel management in universities, thereby contributing to the achievement of strategic goals for institutional development. The proposed academic staff evaluation system can be implemented at both the university and national levels. Its implementation will further foster a competitive environment among academics at the national, university, faculty, and departmental levels.
Keywords: teachers and research staff evaluation; evaluation criteria; academic efficiency; teacher ranking; academic portfolio